Silicon mitigates the adverse effects of drought on Lolium perenne physiological, morphometric and anatomical characters - Grażyna Mastalerczuk; Barbara Borawska-Jarmułowicz; Marzena Sujkowska-Rybkowska; Magdalena Bederska-Błaszczyk; Wojciech Borucki; Piotr Dąbrowski (PeerJ)
Limited water resources and natural drought may result in reduced water availability for the population’s needs and the maintenance of the proper vegetation condition. Understanding the impact of drought on turfgrass species is essential to developing strategies that enhance the adaptability of plants to drought stress. It is vital for maintaining green areas in cities under changing climatic conditions. Therefore, studies on the ability of turfgrasses to recover after periods of drought without irrigation are becoming increasingly essential. We conducted research to determine the possibility of reducing the negative impact of drought stress on the photosynthetic efficiency, the morphometric features of plant shoots and roots, and the distribution of biomass of Lolium perenne lawn cultivars in the initial period of growth by applying biostimulant with silicon. We also investigated how drought and silicon (Si) application affect the leaf and root anatomical structure of L. perenne plants. Studies on the influence of drought on the physiological, biometric parameters and anatomical characteristics of two L. perenne cultivars were carried out under two levels of soil moisture (well-watered plants—control and drought caused by the cessation of watering) and also two variants of Si application (with and without Si application). Plants were exposed to drought in the tillering phase for 21 days. After this time, all plants were provided with optimal soil moisture conditions for the next 14 days (recovery period). Measurements of physiological parameters and biometric features of plants were evaluated in four terms: after 7, 14 and 21 days of drought and after recovery. Drought stress in L. perenne cvs. resulted in decreasing values of physiological parameters, especially maximal fluorescence, the quantum efficiency of photosystem II and photosynthetic electron transport rate compared with the values of features in well-watered plants. These adverse impacts were reflected in decreased biomass-related traits: shoot number, shoots and roots biomass, as well as area and length of roots. The application of Si reduced the detrimental effects of drought by accelerating plant growth after stress and increasing the values of most of the investigated physiological parameters. Under drought stress conditions, Si application led to the development of two-cell-layer exodermis, which reduced the water losses in L. perenne roots and shoots and, as a result, improved the drought tolerance of plants.